(untitled) (Boston, 2005)
Contemporary Japanese Literature: An Anthology Of Fiction, Film, And Other Writing Since 1945 is a collection of some of the finest written works in Japan, offering English translations of stories by nearly two dozen authors. Selected by editor and Harvard professor emeritus of Japanese literature Howard Hibbett, Contemporary Japanese Literature is the perfect smorgasbord to experience post-World War II Japanese writings. Contemporary Japanese Literature is particularly recommended for college library shelves and personal literature collections.
Keywords: Japanese literature,Văn học Nhật bản